CONFLICT COMPETENCE AS A KEY ASPECT OF PROFESSIONAL TRAINING OF SPECIALISTS IN SOCIO-ECONOMIC PROFESSIONS (Psychology Travelogs, 2024)
The issue of conflict resolution competence is becoming increasingly relevant in modern society, characterized by high levels of social tension and rising interpersonal and group conflicts. The development of conflictological competence is a critical component of the professional training of specialists in social sciences. Psychologists, social workers, educators, and other professionals in this field often encounter situations where effective conflict resolution is crucial for their work. The inability to manage conflicts can lead to reduced work quality, loss of client trust, and even emotional burnout.Modern professional training requires not only theoretical knowledge but also the development of practical skills for constructive conflict resolution, emotional resilience, empathy, and the ability to interact effectively with others in complex situations. This issue becomes particularly significant in the context of educational system reforms, which focus on a competency-based approach, where conflictological competence is seen as a key element for professionals in social fields. An analysis of scientific literature indicates a sustained interest in studying the different aspects of conflict emergence and the search for ways to resolve and prevent conflicts. Effective conflict management or prevention is an essential component of conflictological competence in its general understanding.This paper discusses various perspectives on conflictological competence, with an emphasis on its role in enhancing professional effectiveness, especially for specialists who frequently deal with interpersonal and social conflicts. It highlights the importance of practical skills in working with conflict situations, enabling future professionals to understand, predict, and resolve conflicts constructively. The article underscores that the development of this competence is fundamental for improving the quality and efficiency of professional activities in the social sciences.
Keywords: conflict; conflict competence; conflictological competence; components of conflictological competence; specialists of socionomic professions